Study On Maternal & Fetal Outcome Of Jaundice Pregnancy (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Pregnancy with jaundice is regarded as high risk pregnancy so it is considered very important sign during antenatal check up. It complicates pregnancies and is one of the important causes of maternal and neonatal morbidity and mortality worldwide. Viral hepatitis is the most frequent cause of jaundice associated with pregnant woman.Objective: To assess the maternal & fetal outcome of jaundice in pregnant womenMethods: This study was a cross sectional study carried out Department of Obstetrics and Gynaecology, Dhaka National Medical College Hospital, Dhaka From April 2016 to September 2017. All diagnosed cases of pregnancy with jaundice full filing the inclusion and exclusion criteria in the department of Obstetrics and Gynecology, Dhaka National Medical College Hospital, Dhaka. Total 50 sample were taken in this study.Results: Fifty pregnant women the mean age was 24.40±4.32 years. The causes of jaundice during pregnancy were viral hepatitis (82%), obstetrics cholestasis (10%) and HELLP syndrome (8%). The total infective pathology due to hepatitis E (HEV) being the major cause of infection i.e. 42%, followed by Hepatitis Hepatitis B in 32%, Hepatitis C (HCV) in 2%. However, 8% of the mothers were infected with mixed viral hepatitis. Among them 12% underwent caesarean section. Among the neonates of the 47 mothers who recovered, 16% had a neonatal death and 34% had low birth weight.Conclusion: This study shows most hepatitis B (HBV) during third trimester of pregnancy associated with more serious complication than other types of viral hepatitis. It is recommended that women in the reproductive age group (before the first pregnancy) should receive full course of hepatitis B vaccine. Public awareness, complete immunization against viral hepatitis, better sanitation facilities, safe drinking water, increased availability of antenatal care for early detection and well equipped hospitals for intensive care.J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 16-19